2013
DOI: 10.1073/pnas.1304053110
|View full text |Cite
|
Sign up to set email alerts
|

Induction of human cardiomyocyte-like cells from fibroblasts by defined factors

Abstract: Heart disease remains a leading cause of death worldwide. Owing to the limited regenerative capacity of heart tissue, cardiac regenerative therapy has emerged as an attractive approach. Direct reprogramming of human cardiac fibroblasts (HCFs) into cardiomyocytes may hold great potential for this purpose. We reported previously that induced cardiomyocyte-like cells (iCMs) can be directly generated from mouse cardiac fibroblasts in vitro and vivo by transduction of three transcription factors: Gata4, Mef2c, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
277
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(297 citation statements)
references
References 33 publications
14
277
0
2
Order By: Relevance
“…Reprogramming human somatic cells to cardiomyocytes often involves Mesp1 (30,36,37), justifying the identification of effectors downstream of Mesp1. The miRNAs identified here represent early regulators of cardiac fate, likely at the stages of cardiac mesoderm formation and cardiac program initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming human somatic cells to cardiomyocytes often involves Mesp1 (30,36,37), justifying the identification of effectors downstream of Mesp1. The miRNAs identified here represent early regulators of cardiac fate, likely at the stages of cardiac mesoderm formation and cardiac program initiation.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither GMT nor GHMT, which reprogrammed iCMs from mouse fibroblasts, was able to reprogram human fibroblasts into iCMs in vitro [11][12][13]; however, inclusion of additional reprogramming factors resulted in successful reprogramming. Nam et al [12] found that GHT, without MEF2C, but with another transcription factor, myocardin, and two muscle-specific miRNAs, miR-1 and miR-133, could reprogram human fibroblasts into iCMs.…”
Section: Direct Cardiac Reprogramming In Human Fibroblastsmentioning
confidence: 99%
“…These reprogrammed iCMs expressed multiple cardiac genes, developed sarcomere-like structures, and generated Ca 2+ transients with a small subset of the cells exhibiting spontaneous contractility after 11 weeks in culture. Wada R. et al [13] reported that GMT with MESP1 and myocardin could activate cardiac gene expression in human neonatal and adult cardiac fibroblasts. In our study, pairing GMT with ESRRG and MESP1 induced global expression of cardiac genes and shifted the phenotype of human fibroblasts toward the CM-like state.…”
Section: Direct Cardiac Reprogramming In Human Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next analyzed whether human fi broblasts could be directly converted to iCMs by defi ned factors [ 17 ]. We found that GMT was not suffi cient for cardiac induction in HCFs.…”
Section: Gata4/mef2c/tbx5/myocd/mesp1 Reprogram Human Fibroblasts Intmentioning
confidence: 99%